2022
DOI: 10.1186/s13059-022-02608-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and functional annotation of chromatin-enriched noncoding RNAs in rice during somatic cell regeneration

Abstract: Background Plants have the remarkable ability to generate callus, a pluripotent cell mass that acquires competence for subsequent tissue regeneration. Global chromatin remodeling is required for this cell fate transition, but how the process is regulated is not fully understood. Chromatin-enriched noncoding RNAs (cheRNAs) are thought to play important roles in maintaining chromatin state. However, whether cheRNAs participate in somatic cell regeneration in plants has not yet been clarified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 124 publications
1
12
0
Order By: Relevance
“…In this study, 6002 rice candidate lncRNAs were identified. The number of lncRNAs was about twice as many as lncNATs, and the proportion was similar to the results reported by Zhang [ 63 ]. This group of lncRNAs may be informative for functional genomic studies in rice, especially regarding the mechanisms associated with seed aging.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, 6002 rice candidate lncRNAs were identified. The number of lncRNAs was about twice as many as lncNATs, and the proportion was similar to the results reported by Zhang [ 63 ]. This group of lncRNAs may be informative for functional genomic studies in rice, especially regarding the mechanisms associated with seed aging.…”
Section: Discussionsupporting
confidence: 89%
“…LncRNA can regulate target genes in cis- and trans-ways, and the corresponding analysis methods of co-localization and co-expression can be used to predict the function of lncRNAs [ 40 , 41 , 46 , 63 ]. Many studies have been reported based on the cis-regulated target genes of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an overrepresentation of 24 nt siRNAs was associated with SE synchronism (Zhang et al, 2014). Thus, as noted by Dal Santo et al, (2022), a readjustment of 24 nt siRNAs appears to be essential for embryogenic commitment.…”
Section: Other Ncrnasmentioning
confidence: 61%
“…Recently, chromatin-enriched ncRNAs (cheRNAs) were identified as positive regulators of genes related to somatic cell reprogramming, being required for cell dedifferentiation and plant regeneration ability in rice ( Zhang et al., 2022 ).…”
Section: Other Ncrnasmentioning
confidence: 99%